2023
DOI: 10.23922/jarc.2022-077
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Coagulofibrinolytic Markers for Postoperative Prediction of Venous Thromboembolism in Colorectal Surgery Patients: A Retrospective Observational Study

Abstract: Objectives: A low rate of the incidence of venous thromboembolism (VTE) after surgeries that are preoperatively classified as having high risk of VTE has been reported in recent years. We seek to identify the optimal cases to receive perioperative pharmacologic thromboprophylaxis. In this study, we evaluated the incidence rate of VTE among patients undergoing colorectal surgery who did not receive perioperative pharmacologic thromboprophylaxis, and the ability of coagulofibrinolytic markers to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Thrombin-antithrombin Complex (TAT), Plasmin α2 Antiplasmin Complex (PIC), Thrombomodulin (TM), and Tissue Plasminogen Activator-inhibitor Complex (t-PAIC) are reliable thrombotic markers that accurately detect changes in the coagulation system in clinical patients undergoing thrombosis detection studies. A retrospective study conducted in Japan demonstrated that TAT can predict the development of DVT in postoperative colorectal cancer patients [3] . TAT is a reliable indicator of thrombin and antithrombin in a ratio of 1:1.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin-antithrombin Complex (TAT), Plasmin α2 Antiplasmin Complex (PIC), Thrombomodulin (TM), and Tissue Plasminogen Activator-inhibitor Complex (t-PAIC) are reliable thrombotic markers that accurately detect changes in the coagulation system in clinical patients undergoing thrombosis detection studies. A retrospective study conducted in Japan demonstrated that TAT can predict the development of DVT in postoperative colorectal cancer patients [3] . TAT is a reliable indicator of thrombin and antithrombin in a ratio of 1:1.…”
Section: Introductionmentioning
confidence: 99%